EFFECTIVE USE OF LIQUID EXTRACTANTS IN THE SEPARATION OF GAS MIXTURES FORMED DURING PYROLYSIS (International journal of artificial intelligence, 2025)
The separation of gas mixtures generated during pyrolysis is a key step in improving the efficiency and environmental sustainability of thermal decomposition processes. The effective use of liquid extractants offers a promising approach to selectively absorb and recover valuable components from complex gas streams. This paper discusses the principles of extraction, evaluates the physicochemical properties of extractants, and examines experimental and industrial data on their application. The study highlights the role of solvent selectivity, mass transfer kinetics, and thermodynamic stability in achieving high separation efficiency. The findings can contribute to the optimization of pyrolysis gas treatment technologies for both energy recovery and pollution control.